Building a Sustainable Society: A Comprehensive Exploration from Circular Economy to Eco-Friendly Practices - Jain, Trilok Kumar (International Journal of Advanced Research in Peace, Harmony and Education, 2023)
In the wake of escalating environmental degradation, it is imperative to transition towards a sustainable society that harmonizes with nature rather than exploits it. This article delves into the multifaceted aspects of building a sustainable society, emphasizing the need for a paradigm shift in societal values and policies. Furthermore, the article underscores the pivotal role of education, particularly in engineering disciplines, in fostering the skills essential for sustainability. It highlights the necessity of integrating sustainability courses into curricula to cultivate a mindset that prioritizes environmental responsibility. The enforcement of pollution abatement measures, both at the national and global levels, emerges as a critical step towards mitigating the impact of industrialization. The article cites instances from China and India, showcasing the role of legal systems and proactive initiatives in curbing environmental harm. Additionally, the delicate balance between energy needs and environmental conservation is explored, advocating for a reduction in energy consumption and the development of eco-friendly technologies. Addressing industrial waste disposal and promoting sustainable consumption are identified as key pillars in the construction of a sustainable society. The article emphasizes the urgency of stringent actions against industries neglecting proper waste disposal systems, as well as the need for a collective effort to regulate consumption patterns and reduce resource exploitation. Moreover, the shift towards eco-friendly products and transparent value chains is discussed as an evolving trend driven by consumer demand and corporate responsibility. The article predicts the potential upheaval in traditional industries, exemplified by the transformation in Sivakasi, India, known for its firework manufacturing, and highlights the necessity for businesses to adopt transparent and environmentally conscious practices.